The lying days - Gordimer, Nadine, 1923-2014 (Bloomsbury, 2002)
Helen lives in a white community near a South African gold mine, at ease with the values of that enclosed world. Then, bohemian student life in Johannesburg and a passionate love affair give Helen the strength to leave behind those "lying days" of youth.